Magnetic resonance imaging validation of medial transthyroid ultrasound-guided stellate ganglion block: A pilot study - Chung, Boo Young; Holfelder, Christian; Feldmann, Robert Enrico; Kleinböhl, Dieter; Raum, Bernhard; Benrath, Justus (Pain practice, 2022)
Objective Ultrasound-guided stellate ganglion block (usSGB) facilitates improved accuracy of needle position and application of lesser volumes of local anesthetic (LA). Approaches of usSGB, however, have not fully been optimized with respect to efficacy and technical convenience. This pilot study examined the anatomical position and spatial distribution of a small volume of LA injectate dispensed by medial transthyroid usSGB via magnetic resonance imaging (MRI) and assessment of its effect on cervical sympathetic nerves. Methods Twelve healthy males were tested in a double-blinded within-subject design. In a total of 37 usSGB, 3 ml of LA and saline 0.9% solution were injected intramuscularly into the longus colli muscle (LCM) preventing uncontrollable spread of LA within cervical structures. Immediately after injection, distribution of injectate was traced by MRI. Twenty-four out of the 37 usSGB-injections with 3 ml ropivacaine 1% (verum) and saline 0.9% (placebo) were compared. Efficacy of usSGB was assessed by the appearance of oculosympathetic paresis and increases in skin temperature. Results All usSGBs were positioned in the proximity of the LCM muscle belly. Most of the axial injectate was distributed within the transversal plane between the middle section of C5 and the upper section of T1 vertebra. Signs of oculosympathetic paresis and skin temperature increase were found exclusively under verum conditions. Conclusion This pilot study demonstrated the feasibility of medial transthyroid usSGB using an out-of-plane technique and a volume of 3 ml of LA. Further studies are required to establish the relative value and safety of this technique compared to other published approaches.